Lipid particles/droplets of the yeast Saccharomyces cerevisiae revisited: Lipidome meets Proteome - Grillitsch, Karlheinz (Elsevier Pub. Co, 2011)
In the yeast Saccharomyces cerevisiae as in other eukaryotes non-polar lipids are a reservoir of energy and building blocks for membrane lipid synthesis. The yeast non-polar lipids, triacylglycerols (TG) and steryl esters (SE) are stored in so-called lipid particles/droplets (LP) as biologically inert form of fatty acids and sterols. To understand LP structure and function in more detail we investigated the molecular equipment of this compartment making use of mass spectrometric analysis of lipids (TG, SE, phospholipids) and proteins. We addressed the question whether or not lipid and protein composition of LP influence each other and performed analyses of LP from cells grown on two different carbon sources, glucose and oleate. Growth of cells on oleate caused dramatic cellular changes including accumulation of TG at the expense of SE, enhanced the amount of glycerophospholipids and strongly increased the degree of unsaturation in all lipid classes. Most interestingly, oleate as a carbon source led to adaptation of the LP proteome resulting in the appearance of several novel LP proteins. Localization of these new LP proteins was confirmed by cell fractionation. Proteomes of LP variants from cells grown on glucose or oleate, respectively, were compared and are discussed with emphasis on the different groups of proteins detected through this analysis. In summary, we demonstrate flexibility of the yeast LP lipidome and proteome and the ability of LP to adapt to environmental changes.